Realizing Quality Global Learning Through a Training Model for Improving Self-Regulated Learning (SRL) Skills for International Class Program Students - Budi Purwoko; Ima Widiyanah; Ricky Setiawan; Ach. Sudrajad Nurismawan (Universitas PGRI Yogyakarta, 2025)
The constraints of learning management skills and environmental adaptation are often faced by new students, including students who are in the international class program. But sometimes, students are not given psychological assistance to be able to overcome their problems. This research aims to produce a training model to improve Self-Regulated Learning (SRL) for international class students to be able to adapt and survive in undergoing high academic demands. Using the 4-D development (Define, Design, Develop, Disseminate), the SRL improvement training model for international class students of the Faculty of Education, Surabaya State University has been validated by 2 experts and 3 lecturers as potential users and tested its effectiveness through a quasi-experiment with 40 students. The results found that the SRL improvement training model for international class students has met the aspects of acceptability and is empirically proven to improve SRL skills. This finding can be followed up by disseminating to all faculties that have international class programs at Surabaya State University and adapting it to the campus's Learning Management System (LMS) to make it more accessible. Keywords: international class students, self-regulated learning, skills